The spatial–temporal interaction in the LTP induction between layer IV to layer II/III and layer II/III to layer II/III connections in rats' visual cortex during the development. (14th May 2017) - Li, Da-Ke; Zhang, Chao; Gu, Yu; Zhang, She-Hong; Shi, Jian; Chen, Xian-Hua
Highlights: The amplitudes of H-LTP decrease more quickly than that of V-LTP after eye opening. A pre-formed V-LTP can facilitate the induction of H-LTP before eye opening. A pre-formed H-LTP has a much lesser influence on V-LTP induction. Abstract: During the early developmental period, long-term potentiation (LTP) can be induced in both vertical and horizontal connections in the rat visual cortex. However, the temporal difference in LTP change between the two pathways during animal development remains unclear. In this study, LTP in vertical (from layer IV to layer II/III) and horizontal (from layer II/III to layer II/III) synaptic connections were recorded in brain slices from the same rats, and the developmental changes of LTP in both directions were compared within the animals' eye-opening period. The results showed that the LTP amplitudes declined to unobservable levels on P16 in the horizontal connections and on P20 in the vertical synaptic connections. Meanwhile, V-LTP (LTP induced in the vertical direction) was always stronger than H-LTP (LTP induced in the horizontal direction) under the same conditions of pairing stimulus (PS). Next, H-LTP and V-LTP were induced from the same neuron in layer II/III to determine the spatiotemporal interactions between layer II/III horizontal inputs and ascending synaptic inputs during the maturation of rat visual cortex. The data show that the weak PS, which failed to induce H-LTP alone, was able to induce H-LTP effectively while V-LTP was performed on P10. Our results suggest that V-LTP can strengthen H-LTP induction in the visual cortex during the early developmental period. In contrast, the regulatory effect of H-LTP on V-LTP was much weaker.